Perbedaan Prenatal Yoga dengan Knee Chest terhadap Perubahan Posisi Janin Sungsang ke Normal pada Kehamilan TM III di Klinik Cibodas - halida inayah; Retno Widowati; Febry Mutiariami Dahlan (Universitas Baiturrahim, 2023)
Breech position is one of the four main indications for caesarean section worldwide. This breech location can occur in 3-4% of all deliveries. A breech delivery gives a poor prognosis because it increases the risk of complications for the mother and fetus. There are two ways to manage a breech pregnancy, namely knee chest and external version, but there are physical exercises that can provide abdominal space so that it gives the baby the opportunity to rotate, namely prenatal yoga activities. The purpose of this study was to determine the difference between prenatal yoga and knee chest in changing the position of the breech fetus to normal. The methodology of this research is using post test with control group design. The study population was pregnant women in the third trimester with a breech position as many as 42 people. The sampling technique used purposive sampling as many as 30 people into samples which were divided into 2 groups, namely 15 experimental group (prenatal yoga) and 15 control group (knee chest). The research instrument used the results of Ultrasonography and observation sheets. Data analysis used the Mann-Whitney Test. The results showed that there was a difference in the average time needed to change the position of the fetus by doing prenatal yoga and knee-chest. Prenatal yoga takes a shorter time (10 days) while knee-chest takes longer (15 days) so that prenatal yoga is more effective for pregnant women in improving fetal presentation. Bivariate results showed a ( p-value of 0.002 < 0.005). Conclusions based on the results of the study there was a difference in the average time required to change the position of the fetus by doing prenatal yoga and knee-chest. Prenatal yoga takes a shorter time while knee-chest takes longer to help turn the fetal presentation into a head so that prenatal yoga is more effective in helping to improve fetal presentation.